“A Day Without Immigrants” - Benita Heiskanen (European Journal of American Studies)
This article considers the debates surrounding the “Day Without Immigrants” protests organized in major U.S. cities on 1 May 2006, prompted by H.R. 4437, the Border Protection, Anti-Terrorism, and Illegal Immigration Control Act of 2005, from the multiple perspectives of scholars, pundits, policy makers, and participants. Although much of these debates ostensibly centered around illegal Latino/a immigration to the United States, underneath the discussion ran a curious ideological thread, one that invoked groups’ right to be in the United States in the first place. The article argues that the rhetoric used in these discourses pitted various class-based ethnoracial groups against each other not so much to tackle the proposed immigration bill but, rather, to comment on the ramifications of an increasingly multiracial United States.